Incidence of Glaucoma in Type 2 Diabetes Patients Treated With GLP‐1 Receptor Agonists: A Systematic Review and Meta‐Analysis - Maheen Asif; Aliza Asif; Ummi Aiman Rahman; Hanzala Ahmed Farooqi; Oshaz Fatima; Waqar Ali; Uzair Jafar; Mohammed Hammad Jaber (Endocrinology, Diabetes & Metabolism)
ABSTRACT Aims Glaucoma, a leading cause of irreversible blindness, is particularly prevalent among individuals with Type 2 Diabetes Mellitus (T2DM), a known risk factor for the disease. This systematic review and meta‐analysis aimed to evaluate the incidence of glaucoma in T2DM patients treated with Glucagon‐Like Peptide 1 Receptor Agonists (GLP‐1RAs) compared to those using other antihyperglycaemic agents. Materials and Methods A comprehensive search of literature was conducted using MEDLINE (PubMed), the Cochrane Library, Google Scholar, and Scopus up to September 14, 2024. Observational studies that reported the incidence of glaucoma among T2DM patients using GLP‐1RAs versus other antihyperglycaemic drugs were included. Data analysis employed the random‐effects model, presenting odds ratios (OR) with 95% confidence intervals (CI). Heterogeneity was assessed using I2 statistics, and a sensitivity analysis was performed to test the result's robustness. Results Five observational studies involving 2,500,430 participants met the inclusion criteria. The meta‐analysis indicated that GLP‐1RA use was associated with a nonsignificant reduction in the incidence of glaucoma (OR: 0.78; 95% CI: 0.60 to 1.02; p = 0.01: I2 = 88%). Sensitivity analysis by leave‐one‐out method showed a significant reduction of glaucoma in GLP‐1 RA users. Conclusions In conclusion, GLP‐1RA usage in T2DM patients may be beneficial in lowering the risk of glaucoma under some circumstances. These results advocate for further clinical studies to confirm GLP‐1RAs' protective ocular effects, potentially influencing future treatment guidelines and preventive care strategies for glaucoma patients.